Crosslinked domains of apoA-I but not of ΔK107, are involved in rHDL´s shape - Díaz Ludovico, Ivo (2018)
Human apolipoprotein A-I (ApoA-I) is the major protein component of high density lipoproteins (HDL) playing a pivotal role in reverse cholesterol transport. A natural mutant of ApoA-I having a deletion of the single residue Lys107 (K) induces severe atherosclerosis. The structural and functional effects due mutation are studied to elucidate the pro-atherogenicity of this protein. In this study we investigate the structural effects of K107 deletion in a comparative approach with wild type (W) protein. Attending to structural alterations caused by deletion we have crosslinked with BS3 the lysine residues of both proteins in the native monomeric state (KBS3 and WBS3). Tryptophan fluorescence is red shifted in the deletion mutant (K or KBS3) compared with the wild type protein (W or WBS3) but it is not affected by crosslinking. The micellization of multilamellar DMPC liposomes (145:1 molar ratio) was evaluated with crosslinked (WBS3 and KBS3) and un-crosslinked proteins. The rate of the micellization process was decreased by the crosslinking although the efficiency of the process at final point was not affected. The size of HDL complexes formed by DMPC micellization were determined by polyacrylamide native electrophoresis and shape was visualized by TEM. Crosslinked proteins do not form the small sized populations of lipoprotein complexes observed with uncrosslinked proteins. TEM observation indicates that generation of discoidal complexes is decreased by crosslinking of the wild type protein but is less affected in the case of the deletion mutant. Thus, we can conclude that the ability to generate discoidal HDL complexes is reduced exclusively by crosslinking of lysine 107.